ABOUT THE FUNERAL RITE IN THE EARLY IRON AGE (Scientific journal of the Fergana State University, 2024)
This article, based on the results of archaeological research conducted at the Khanabad-1 monument and a critical analysis of the scientific literature covering this issue, presents burial rites in the Fergana Valley of the Early Iron Age. The monument separately lists the characteristic features of the mounds discovered during the last three field surveys. The funeral rite of the period under study shows that the preparation of each grave and the burial of the deceased had its own peculiarity.